Activation characteristics of Ty3-retrotransposons after spaceflight and genetic stability of insertion sites in rice progeny - Yang, Qing; Chen, Lishan; Zhang, Meng; Wang, Wei; Zhang, Binquan; Zhou, Dazhuang; Sun, Yeqing (Frontiers in Plant Science, 2024)
The space environment is mutagenic and may induce genomic and phenotypic variations. To analyze the activation characteristics of Ty3-retrotransposons and genetic stability of insertion sites in rice progeny after spaceflight, seeds of Nipponbare, DN416, and DN423 were exposed on board the SJ-10 recoverable satellite for 12.5 days. The study found that the retrotransposons of ancient and young transposon families underwent demethylation from the tillering to heading stages of Nipponbare plants, which were F0 generation of space-exposed seeds, when the Nipponbare seeds were hit by single space high charge and energy (HZE) particles with LET ≥ 100 keV/μm. the transcription levels significantly increased in ancient transposon families (osr30, osr40, and rire10) and young transposon families (dagul, rn215-125, osr37, RLG_15, osr34, rire8, rire3, rire2, and hopi) (p ≤ 0.05) when LET > 100 keV/μm. Furthermore, the young Ty3-retrotransposons, which included the hopi, squiq, dasheng, rire2, rire3, rire8, osr34, rn_215-125, dagul, and RLG_15 families, underwent 1 to 8 transpositions in the F3 to F5 of DN416 and DN423 mutants, and some of these transposon insertion sites were stably inherited. The research holds great significance for understanding the activation characteristics of Ty3-retrotransposons in the rice genome induced by space radiation and the genetic characteristics of transposon insertion sites in its progeny.